2009
DOI: 10.1016/j.econlet.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the distribution of congressional earmarks across states

Abstract: Congressional earmarks have been the subject of significant political debate in recent years. Also known as "pork barrel spending," earmarks are budgetary requests made by a single legislator that typically circumvent the traditional competitive bidding process designed to ensure the efficient use of public dollars. Utilizing annual state-level estimates of pork barrel spending, we briefly examine the factors influencing states' receipt of earmarked funds from Congress. Results indicate that on average smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Similar results have been found for the allocation of federal highway demonstration grants (Gamkhar and Ali ) and for federal spending in states in general (Atlas et al. ; Boyle and Matheson ; Hoover and Pecorino ).…”
Section: Previous Worksupporting
confidence: 80%
“…Similar results have been found for the allocation of federal highway demonstration grants (Gamkhar and Ali ) and for federal spending in states in general (Atlas et al. ; Boyle and Matheson ; Hoover and Pecorino ).…”
Section: Previous Worksupporting
confidence: 80%
“…It can be an indicator to reflect political considerations. For instance, Boyle and Matheson (2009) find that the federal government tends to pay more attention to the key states than other states during the presidential election period. In the empirical implementation section, we will use the number of committee members (or candidates) that each province has in the Central Committee of the Communist Party of China as a proxy variable for the political motivation in the regional allocation of public investment made by the Chinese central government.…”
Section: Social Choice Rulementioning
confidence: 99%
“…To date, scholars have regional investment from both political and economic perspectives. Regarding political factors, scholars such as Atlas et al (1995), Wallis (1998), Fleck (2001), Wu (2007), and Boyle and Matheson (2009) concluded that a state in the United States appears to obtain more federal investments if that state has more per capita representatives in the legislative bodies and more congressional delegates, or if ve a higher level of seniority and belonged to the same clan as the president. Cadot et al (1999), using a panel of 21 French regions in 198521 French regions in -1991, found that pork-barrel politics are significant determinants of the cross-regional transportation infrastructure investments.…”
Section: Introductionmentioning
confidence: 99%
“…First, anticipation about how parties behave in periods distant from elections creates a different pay-off structure for partisan supporters and marginal voters when they make their electoral choices. As Bueno de Mesquita et al (2004) note, the expectation of future rewards is what makes partisan voters loyal. When their expectation is fulfilled, those voters continue to maintain support for their party.…”
Section: Time-varying Allocation Strategymentioning
confidence: 96%
“…Legislative bargaining to promote his agenda further motivates a president to allocate benefits to members of his own party (Groseclose and Snyder, 1996). In particular, districts are awarded more pork when represented by powerful senior figures (Boyle and Matheson, 2009;Levitt and Poterba, 1999;Moore and Hibbing, 1996) or by members of the relevant committees (Alvarez and Saving, 1997;Arnold, 1979;Engstrom and Vanberg, 2010;Heitshusen, 2001;Knight, 2005;Lauderdale, 2008;Ray, 1981). 1 1 On the other hand, Anzia andBerry (2011), Berry et al (2010), and Lauderdale (2008) present evidence suggesting that the number of terms has no significant effect over the allocation of federal outlays.…”
Section: Time-varying Allocation Strategymentioning
confidence: 99%